EXPRESSION OF GROWTH HORMONE (PhGH) GENE AND ANALYSIS OF INSULINE-LIKE GROWTH FACTOR I (IGF-I) PRODUCTION IN AFRICAN CATFISH (Clarias gariepinus) TRANSGENIC F-1 - Huria Marnis; Bambang Iswanto; Rommy Suprapto; Imron Imron (Indonesian Aquaculture Journal, 2013)
We have previously produced F-1 transgenic of African catfish from crosses between founder transgenic female and non transgenic male. The aim of this study was to evaluate distribution and expression PhGH growth hormone gene transgenic African catfish organs and to measure the concentration of IGF-I in plasma. Transgene was detected using the PCR method in various organs, namely pituitary, brain, liver, heart, spleen, kidney, intestine, stomach, muscle, gill, and eye. Transgene expression levels were analyzed using the method of quantitative Reverse Transcriptase-Polymerase Chain Reaction (qRT-PCR). Plasma samples were analyzed for Insuline-like Growth Factor (IGF-I) using Enzyme Linked Immunosorbent Assay (ELISA) method. The results showed that the PhGH was detected and expressed in all organs of the transgenic African catfish (F-1). Liver exhibited the highest level of PhGH mRNA (23 x 106 copies). The plasma IGF-I levels in transgenic individuals were not significant than non transgenic. The higher level of exogenous PhGH gene expression may not represent the production of IGF-1.